Use of Potentially Reduced Exposure Tobacco Products Among American Indian Smokeless Tobacco Users: Associations With Cessation Behaviors and Cotinine Levels. (January 2020) - Comiford, Ashley L.; Rhoades, Dorothy A.; Dvorak, Justin D.; Ding, Kai; Mehta, Toral; Spicer, Paul; Wagener, Theodore; Doescher, Mark P.
Objectives: American Indian/Alaska Native (AI/AN) adults use smokeless tobacco products (eg, chewing and dip tobacco) more often than other racial/ethnic groups do. Although US adults increasingly use potentially reduced exposure tobacco products (PREPs), such as electronic cigarettes and snus, no studies have examined the use of PREPs among AI/AN smokeless tobacco users. We examined associations between current PREPs use and smokeless tobacco–related measures, including cessation attempts and cotinine levels, in a sample of American Indian adults who currently use smokeless tobacco. Methods: We collected survey and tobacco biomarker data from 299 adult American Indian smokeless tobacco users at Cherokee Nation health care facilities and events in 2016 and 2017. We used multivariable analyses to determine associations between current PREPs use and smokeless tobacco–related characteristics. Results: Current PREPs users were younger, less likely to be married or living with a partner, less likely to report a chronic medical condition, and more likely to report other tobacco use than PREPs nonusers. Among participants with annual household incomes ≤$30 000, current PREPs users were less likely than PREPs nonusers to report a definite desire to quit smokeless tobacco ( P = .02). PREPs use was not associated with planning to quit smokeless tobacco, past 12-month smokeless tobacco quit attempts, amount of smokeless tobacco used per week, cotinine levels, or scores on the Fagerström Test for Nicotine Dependence–Smokeless Tobacco. Conclusions: Our study suggests that American Indian smokeless tobacco users may not be using PREPs as a smokeless tobacco cessation aid. Future studies should take this finding into consideration when evaluating the role of PREPs use in smokeless tobacco cessation and in total tobacco cessation in this population.